EXPLORING THE IMPLEMENTATION OF KNOWLEDGE MANAGEMENT IN VILLAGE TOURISM: CASE STUDY IN KAMPUNG ARAB SURABAYA - Amalia Lestari; Nadya Ananda Tri Anugrah Putri; Meer Zhar Farouk Amir Razli; Huda Hamidon; Nik Nur Izzati Nik Rosli (International Journal of Accounting, Finance and Business, 2023)
Indonesia is an archipelago that has a diversity of natural beauty, culture, customs, and languages that make Indonesia famous internationally in the field of tourism. Among its famous attractions is Kampung Arab in Surabaya's Ampel area, a captivating tourist village. Remarkably, Kampung Arab continues to innovate and develop its tourism independently, without government cooperation. Knowledge management plays a crucial role in maximizing the potential of such villages. This study employed a qualitative approach through interviews conducted with several authorities in Kampung Arab, based on their knowledge and experience in managing the village's tourism. The interviews focused on gathering insights and perspectives regarding knowledge management practices, challenges, and prospects. Thematic analysis was employed to identify and interpret patterns and themes in the qualitative data. The study incorporates Wiig's knowledge management cycle, Nonaka & Takeuchi's knowledge management model, knowledge capture, and Piktialis and Greenes's knowledge transfer cycle. Findings show that part of the model and concept of knowledge management have been implemented in Kampung Arab such as importing and storing knowledge from experts. However, the authorities must take on challenges and seize opportunities based on the analysis of the knowledge management model and concept as a whole to ensure that Kampung Arab remains a viable tourist destination.